2005
DOI: 10.1063/1.2076428
|View full text |Cite
|
Sign up to set email alerts
|

O 2 ( Δ 1 ) production in flowing He∕O2 plasmas. II. Two-dimensional modeling

Abstract: In conventional chemical oxygen-iodine lasers ͑COIL͒ the 1.315 m transition in atomic iodine is pumped by a sequence of reactions of I 2 and I with O 2 ͑ 1 ⌬͒ which is generated using liquid chemistry. Ongoing studies are investigating means to produce the O 2 ͑ 1 ⌬͒ precursor with an electric discharge ͑eCOIL͒ to enable a totally gas phase system. Due to the thermodynamic and power loading requirements, the plasma in eCOIL systems is sustained in a flow of a rare-gas diluent and the O 2 . In previous investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 10 publications
(7 reference statements)
0
14
0
Order By: Relevance
“…The velocity flow field for the neutral gas, which is treated as a single fluid, is calculated using a newly developed incompressible flow option within the fluid dynamics model described in [25]. This option is implemented using an artificial compressibility [26,27] technique in which the momentum equation is solved with a pseudo-continuity equation having pressure p acting as a relaxation parameter.…”
Section: Description Of the Modelmentioning
confidence: 99%
“…The velocity flow field for the neutral gas, which is treated as a single fluid, is calculated using a newly developed incompressible flow option within the fluid dynamics model described in [25]. This option is implemented using an artificial compressibility [26,27] technique in which the momentum equation is solved with a pseudo-continuity equation having pressure p acting as a relaxation parameter.…”
Section: Description Of the Modelmentioning
confidence: 99%
“…However the energy efficiency of the O 2 (a 1 g ) production drops to ∼10-12% because the electron energy starts to dissipate into other channels, mostly in O 2 dissociation. Nevertheless the highest O 2 (a 1 g ) yields were experimentally obtained just in rf discharges [1,[8][9][10][11][12][13][14][15][16][17]. It stimulated us in the experimental and theoretical study of rf discharges to obtain the highest O 2 (a 1 g ) yield at an increased oxygen pressure [3, 9-11, 15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…The long lifetime of O 2 ͑ 1 ⌬͒ ͑60 min͒ and robustness against quenching enables transport over long distances to the laser cavity. [10][11][12][13][14][15][16][17][18][19][20][21][22] Recently, positive gain was reported in atomic iodine resulting from electric discharge produced O 2 ͑ 1 ⌬͒, 23,24 followed by laser demonstrations. 8,9 Recent and ongoing investigations have shown that substantial yields of O 2 ͑ 1 ⌬͒ can be generated by an appropriately tailored electric discharge, typically in mixtures with rare gas diluents such as He.…”
Section: Introductionmentioning
confidence: 99%